2015
DOI: 10.1016/j.appet.2015.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, fitness, and brain integrity in adolescence

Abstract: Objective We set out to ascertain the relationship between insulin resistance, fitness, and brain structure and function in adolescents. Design and Methods We studied 79 obese and 51 non-obese participants who were recruited from the community, all without type 2 diabetes mellitus. All participants received medical, endocrine, neuropsychological, and MRI evaluations as well as a 6-minute walk test that was used to estimate fitness (maximal oxygen consumption). Results Obese adolescents had significantly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 40 publications
10
44
0
1
Order By: Relevance
“…Furthermore, consistent with results from an adult sample, adolescents with BED and obesity and normal‐weight controls attained comparable levels of cognitive flexibility (Kelly, Bulik, & Mazzeo, ). Moreover, no group differences between adolescents with obesity and normal‐weight controls emerged, which is in line with some previous studies in population‐based samples (Gunstad et al, ; Ross et al, ), but contrasts with the findings of lower cognitive flexibility of adolescents with obesity in other studies with population‐based and clinical samples (Maayan et al, ; Verdejo‐Garcia et al, ). Eventually, executive differences between BED, OB, and NW groups might become more apparent in complex everyday situations, which require self‐regulation (Shamosh & Gray, ) and in which binge‐eating episodes are likely to occur (e.g., Elliott et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, consistent with results from an adult sample, adolescents with BED and obesity and normal‐weight controls attained comparable levels of cognitive flexibility (Kelly, Bulik, & Mazzeo, ). Moreover, no group differences between adolescents with obesity and normal‐weight controls emerged, which is in line with some previous studies in population‐based samples (Gunstad et al, ; Ross et al, ), but contrasts with the findings of lower cognitive flexibility of adolescents with obesity in other studies with population‐based and clinical samples (Maayan et al, ; Verdejo‐Garcia et al, ). Eventually, executive differences between BED, OB, and NW groups might become more apparent in complex everyday situations, which require self‐regulation (Shamosh & Gray, ) and in which binge‐eating episodes are likely to occur (e.g., Elliott et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding sustained attention, the BED group did not show difficulties compared to the NW group, indicating healthy levels of sustained attention in adolescents with BED and obesity, which corresponds to first evidence from adults with BED compared to a NW group (Kelly et al ). Confirming previous research in adolescents with obesity (Cserjesi et al, ; Ross et al, ; Verdejo‐Garcia et al, ), the OB group, in contrast, attained lower outcomes in sustained attention than the NW group. However, these differences vanished after controlling for level of education.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…4). This posit is supported by a positron emission tomography–fluorodeoxyglucose study in adults demonstrating that higher BMI is associated with lower baseline prefrontal glucose metabolism (43) as well as previous reports of thinner OFCs (part of the PFC) and diminished performance on various cognitive tasks (visual working memory tasks and digital vigilance tasks) in obese adolescents (44). In keeping with these observations, it has been reported that obese adolescents (mean age 17 years) have higher ratings of disinhibition on the Three Factor Eating Questionnaire, lower performance on the cognitive tests (Stroop color-word score), and lower OFC volume (assessed by MRI) and that disinhibition correlated with BMI, Stroop color-word score, and OFC volume (45).…”
Section: Discussionmentioning
confidence: 63%
“…17 In youth, BMI is most consistently associated with reduced grey matter volume in the frontal lobe (FL), specifically in the prefrontal cortex (PFC) and orbitofrontal cortex (OFC). [17][18][19][20][21][22] There is also evidence of reduced volume of medial temporal lobe (MTL) structures, such as the hippocampus and parahippocampal gyrus in overweight and obese adolescents. 23 The FL regions are of particular relevance to BD because they are associated with higher-level cognitive processes, such as executive functioning, decisionmaking and inhibitory control, and are also known to modulate emotion processing.…”
Section: Introductionmentioning
confidence: 99%